Peningkatan Hasil Belajar Siswa Melalui Media Kotak Sifat Cahaya di Kelas V SDN 09 Palembang - Yuliana, Yuliana (Yayasan Sembilan Pemuda Indonesia, 2025)
The importance of conceptual understanding in science learning on the material of light properties must be further improved because the value of students' conceptual understanding is not only limited to knowing but students are also able to re-explain the material that has been taught in their own language and can apply it in everyday life. Therefore, this study aims to improve the learning outcomes of fifth grade students of SD 09 Palembang on the material of light properties by using light properties box learning media. The method used is Classroom Action Research (CAR) which is carried out in two cycles. The research was conducted at SD Negeri 09 Palembang on July 29, 2024 to August 5, 2024 with the research subjects being 28 fifth grade students of SDN 09 Palembang. Data was collected through observation and tests. Observations were carried out to determine student activities during learning, while tests were carried out to determine student learning outcomes after learning. Based on the results of the study, information was obtained that there was an increase in student learning outcomes who obtained high scores from Cycle 0 as much as 10.71% to cycle 1 as much as 39.28% and cycle 2. The pretest results showed that 71.42% of students had low understanding between 45 and 72. The results of the study also showed an increase in student activity during learning. Although the results of the study showed success, some students still needed additional support to understand more complex concepts. This study suggests the application of more diverse learning media and adaptation of teaching methods to meet the needs of individual students. The use of interactive and experiment-based media allows students to see and experience light phenomena directly, which reinforces the concepts being taught. This study suggests the application of more diverse learning media and adaptation of teaching methods to meet the needs of individual students